2011
DOI: 10.1111/j.1462-2920.2011.02540.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Growth of Aerobic Anoxygenic Phototrophs in the Mediterranean Sea

Abstract: The distribution of aerobic anoxygenic phototrophs (AAPs) was surveyed in various regions of the Mediterranean Sea in spring and summer. These phototrophic bacteria were present within the euphotic layer at all sampled stations. The AAP abundances increased with increasing trophic status ranging from 2.5 × 10(3) cells per ml in oligotrophic Eastern Mediterranean up to 90 × 10(3) cells per ml in the Bay of Villefranche. Aerobic anoxygenic phototrophs made up on average 1-4% of total prokaryotes in low nutrient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
49
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 27 publications
(50 reference statements)
16
49
0
Order By: Relevance
“…This is consistent with the fact that AAP relative abundances were similar for alpine (3 to 22%) and subalpine (4.8 to 23%) lakes (average Ϯ standard deviation [SD], 12.8% Ϯ 7.1%). These values are similar to estimates based on pufM gene frequencies in single-cell genomes in Wisconsin and Maine lakes (20) but significantly higher than percentages of AAPs reported for open-ocean environments (5,6,35,36). …”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This is consistent with the fact that AAP relative abundances were similar for alpine (3 to 22%) and subalpine (4.8 to 23%) lakes (average Ϯ standard deviation [SD], 12.8% Ϯ 7.1%). These values are similar to estimates based on pufM gene frequencies in single-cell genomes in Wisconsin and Maine lakes (20) but significantly higher than percentages of AAPs reported for open-ocean environments (5,6,35,36). …”
Section: Discussionsupporting
confidence: 72%
“…Previous studies with freshwater lakes identified that AAP numbers in various lakes correlate with total phosphorus or chlorophyll content (22), and similar results were also found in marine environments (6,36). Interestingly, we did not observe such correlations in either the seasonal or the altitudinal survey.…”
Section: Discussionsupporting
confidence: 59%
“…These results are in line with those recorded in estuarine systems such as the Long Island Sound, Delaware Bay and Chesapeake Bay, where these bacteria can constitute more than 10 % of the prokaryotic community Schwalbach and Fuhrman, 2005;Sieracki et al, 2006;Waidner and Kirchman, 2008). The low AAP bacterial percentages in-shelf and offshore Beaufort Sea samples were similar to those reported in Antarctic waters of the Southern Ocean (Schwalbach and Fuhrman, 2005) and in most oligotrophic temperate and tropical regions (Hojerová et al, 2011;Jiao et al, 2007;Lamy et al, 2011). This is consistent with the trophic status of the Beaufort Sea that is quite oligotrophic in summer (Ortega-Retuerta et al, 2012), with nearly undetectable nitrate levels during the Malina cruise.…”
Section: Abundance In the Arctic Oceansupporting
confidence: 77%
“…Abundances of AAP bacteria positively correlated with chlorophyll a concentrations in a variety of water bodies [3,[22][23], suggesting that primary productivity may contribute to the abundance of AAP bacteria. Annotated gene content revealed the dependence of incertae sedis Hyphomonadaceae strain UKL13-1 and incertae sedis Betaproteobacterium strain UKL13-2 on carbon and nitrogen fixation from Aphanizomenon flos-aquae [24].…”
Section: Abundances Of Pufm Genementioning
confidence: 97%
“…Sediments of ErH and LGH were similar in the values of pH, OM, TOC, OUT, and SHANNON index, whereas ChH was relatively different. The number of OTUs in each library was ranked as follows: ChH (13) < ErH (19) < LGH (23). The richness (by CHAO and ACE) was ordered as: ChH < ErH < LGH, while for diversity (by SHANNON) it was ChH < LGH < ErH.…”
Section: Diversity Of Pufm Gene Populationsmentioning
confidence: 99%